Study of recycled concrete aggregate as filter media for phosphorus removal in synthetic wastewater - Abd Roni, Norwardatun (2019)
Phosphorus is one of the key nutrients that lead to eutrophication in surface water. However, existing conventional wastewater treatment systems for removing phosphorus are expensive and complex. Recycled concrete aggregate (RCA) may be an alternative solution for phosphorus removal. It can reduce pollution and landfill disposal by converting construction waste into valuable products. This study aims to investigate the physical and chemical characteristics of RCA that influence the removal of phosphorus, as well as the percentage of phosphorus removal using RCAs of two different sizes namely, 5 mm to 10 mm and 25 mm to 30 mm. A total of five vertical laboratory-scale RCA filters were designed and five different concentrations of synthetic wastewater between 10 – 50 mg/L were prepared. The samples taken from the influent and effluent filters were tested and analysed in terms of pH, the uptake capacity of phosphorus (q) and the percentage of phosphorus removal (%). RCA was analysed using Scanning Electron Microscopy (SEM) and Energy-dispersive X-ray spectroscopy (EDX) to determine its chemical composition. The results show that RCA has a high content of aluminium, calcium and magnesium that enhances phosphorus adsorption. RCA measuring between 5 mm to 10 mm in 10 mg/L of synthetic wastewater achieved the highest phosphorus removal percentage of 99.54% at a pH 10. The highest percentage of phosphorus removal achieved was 99.54% in the initial concentration of 10 mg/L by RCA measuring between 5 mm to 10 mm while the lowest percentage of phosphorus removal was 66.25% in the initial concentration of 50 mg/L for RCAs measuring between 25 mm to 30 mm. Furthermore, RCA achieved the highest uptake capacity (q) of 3.45 mg/L in the initial wastewater concentration of 50 mg/L. In conclusion, RCA has the potential to remove phosphorus, particularly in low concentrations of synthetic wastewater and high pH conditions.